Go to my grave - McPherson, Catriona, 1965- (Minotaur Books, 2018)
"Ann Cleeves Donna Weaver has put everything into The Breakers, a Bed and Breakfast that she and her mother are opening on a remote stretch of beach. Now it waits--freshly painted, richly furnished, filled with flowers. But as the guests arrive, they feel like they've been here before. Amid home-baked scones, gorgeous guest rooms, and lavish dinners fit for a king, the feeling of menace grows. Someone has broken their vow. Someone is playing games. And then the games turn deadly..."--